Hubungan Gaya Mengajar Guru Dengan Minat Belajar Siswa di SD Muhammadiyah 2 Limboto Kabupaten Gorontalo - Regina Fandita Ismail (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2026)
The purpose of this research was "To find out how big the relationship is between the teaching style of teachers and students' interest in learning at SD Muhammadiyah 2 Limboto, Gorontalo Regency". This research uses quantitative description research method. The problem in this research is "Is there a relationship between the teaching style of the teacher and the student's interest in learning at SD Muhammadiyah 2 Limboto, Gorontalo Regency". The hypothesis in this study is "There is a significant relationship on the topic of research"The results showed variable Y (students' interest in learning) is influenced by variable X (teacher's teaching style) by 86.57% and 13.43% (the rest) is influenced by other factors not examined in this research. Thus it can be concluded, there is a relationship between the teaching style of teachers and students' interest in learning at SD Muhammadiyah 2 Limboto, Gorontalo Regency. Keywords: Teacher's Teaching Style, Student's Interest in Learning.